2017
DOI: 10.1371/journal.pone.0182554
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-derived physical activity and sedentary time by cancer type in the United States

Abstract: The 2003–2004 and 2005–2006 cycles of the National Health and Nutrition Examination Survey (NHANES) were among the first population-level studies to incorporate objectively measured physical activity and sedentary behavior, allowing for greater understanding of these behaviors. However, there has yet to be a comprehensive examination of these data in cancer survivors, including short- and long-term survivors of all cancer types. Therefore, the purpose of this analysis was to use these data to describe activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
91
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 32 publications
2
91
3
1
Order By: Relevance
“…Taking more activity breaks translates to spending more time in sedentary behaviors and increasing likelihood of taking fewer breaks in sedentary time. These findings are consistent with previous work from NHANES, suggesting that cancer survivors tend to take fewer breaks from their sedentary behavior, despite accumulating similar total daily sedentary time, translating to longer bouts of sedentary behavior compared to those with no cancer history (13). Additionally, BLSA cancer survivors had markedly lower employment rates and higher rates of smoking and comorbidities compared to those without cancer history; factors that warrant further investigation as possible contributors to the degradation of daily PA accrual.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Taking more activity breaks translates to spending more time in sedentary behaviors and increasing likelihood of taking fewer breaks in sedentary time. These findings are consistent with previous work from NHANES, suggesting that cancer survivors tend to take fewer breaks from their sedentary behavior, despite accumulating similar total daily sedentary time, translating to longer bouts of sedentary behavior compared to those with no cancer history (13). Additionally, BLSA cancer survivors had markedly lower employment rates and higher rates of smoking and comorbidities compared to those without cancer history; factors that warrant further investigation as possible contributors to the degradation of daily PA accrual.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have primarily investigated differences in time spent at varying intensities of activity by cancer history, with a focus on meeting Federally-recommended PA guidelines (150 minutes/week in MVPA) (13,18,19). In general, these studies have suggested that cancer survivors largely do not reach recommended PA guidelines and are more likely to engage in light-intensity activities than moderate or vigorous intensity activities (13,18,20). Further, Thraen-Borowski and colleagues showed that total time spent in light-intensity activity was significantly lower while sedentary time was higher in those with cancer history than those with no cancer history (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among colon cancer survivors, physical activity volume declines during cancer therapy and often does not return to pre‐diagnosis volumes after completing therapy . This may explain, in part, why up to 90% of colon cancer survivors do not engage in the recommended minimum volume of 150 min·wk −1 of physical activity . Cross‐sectional studies demonstrate that larger volumes of physical activity are correlated with higher physical and mental wellness, better sleep quality, lower fatigue, less worry about disease recurrence, and better bowel function .…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometers have been established as a valid measure of overall or lifestyle PA in cancer survivors, including BCS (Lynch et al, 2010(Lynch et al, , 2011Pfister et al, 2017;Phillips et al, 2015;Sabiston, Brunet, Vallance, & Meterissian, 2014;Thraen-Borowski, Gennuso, & Cadmus-Bertram, 2017;Vallance, Boyle, Courneya, & Lynch, 2014). Accelerometers have been established as a valid measure of overall or lifestyle PA in cancer survivors, including BCS (Lynch et al, 2010(Lynch et al, , 2011Pfister et al, 2017;Phillips et al, 2015;Sabiston, Brunet, Vallance, & Meterissian, 2014;Thraen-Borowski, Gennuso, & Cadmus-Bertram, 2017;Vallance, Boyle, Courneya, & Lynch, 2014).…”
mentioning
confidence: 99%